2006
DOI: 10.1158/1055-9965.epi-06-0319
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E Expression and Outcome in Pancreatic Ductal Adenocarcinoma

Abstract: The association of high cyclin E expression with poor outcome in some cancers, in particular breast cancer, suggests that it may play an important role in tumor biology. Because the influence of cyclin E expression on outcome is yet to be examined in pancreatic cancer, we assessed the relationship between the expression of cyclin E, p27 Kip1 , and survival in a large cohort of pancreatic cancer patients with long-term follow-up. Expression of cyclin E and p27Kip1 was assessed by immunohistochemistry using tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
3
13
0
2
Order By: Relevance
“…As a crucial regulator for cell cycle progression, increasing data indicated that cyclin E plays a crucial role in PDAC pathogenesis [23]. High cyclin E expression is a strong independent predictor of poor outcome in patients with pancreatic cancer [24]. Here we show that NF45 could regulate cyclin E expression, indicating the oncogenic function of NF45 was at least in part by promoting the expression of cyclin E (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…As a crucial regulator for cell cycle progression, increasing data indicated that cyclin E plays a crucial role in PDAC pathogenesis [23]. High cyclin E expression is a strong independent predictor of poor outcome in patients with pancreatic cancer [24]. Here we show that NF45 could regulate cyclin E expression, indicating the oncogenic function of NF45 was at least in part by promoting the expression of cyclin E (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…The studies by Rosen et al revealed that there was a relationship between the overexpression of cyclin E in the patients with ovary carcinoma and the worse prognosis to varying degrees [7] . In addition, Skalicky et al observed the abnormal overexpression of cyclin E in pancreatic cancer cells [8] . This study also found that in the absence of EPA or DHA, the expression of cyclin mRNA in SW1990 cells was up-regulated, but after treatment with EPA or DHA, real time PCR revealed that the expression of cyclin E was inhibited by both of them in a time-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining authors determined staining levels visually, with obvious potential for incorrect classification especially among the 23 studies (28%), which did not report blinding of the scorers from clinicopathologic details. The high proportion of independently prognostic biomarkers identified by studies using TMAs (44,46,61,85,100,103,116) highlights the importance of this high-throughput methodology allowing appropriate tissue resource rationing but also improving IHC standardization and reproducibility in large cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Including only resections carried out for pancreatic head lesions by PD the median study size was 62 (mean, 80). Eighteen studies only considered patients undergoing PD, with a further 5 including PD subgroup analysis (43,44,85,100,103).…”
Section: Included Studiesmentioning
confidence: 99%